Distributed maximum power point tracking with overvoltage protection for pv systems (2013)
This paper presents an integral solution of the overvoltage problem caused by mismatched conditions when DC-DC converter outputs of PV systems are connected in series, and a distributed maximum power point tracking architecture is implemented. The operating conditions that cause the overvoltage problem are discussed in detail and the consequences of the overvoltage problem are illustrated. The proposed solution is based on a structure that includes a non-linear controller, two linear controllers, and a maximum power point tracking algorithm. Such a solution makes it possible to regulate the PV voltage according to the MPPT controller commands and to limit the DC-DC converter output voltage to avoid damages. The non-linear control structure is experimentally validated with a boost converter and a BP585 PV panel. Simulation results show that the proposed integral solution allows the operation of PV panels in the feasible maximum power point and protects the integrity of the DC-DC converters, avoiding the overvoltage problem caused by mismatched conditions.